Sexual Violence Offenses in Child Forced Marriage Due to Extramarital Pregnancy - Nashriana Nashriana; Putu Samawati; Suci Flambonita; Vera Novianti; Muhamad Sayuti Hassan (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
The enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law) categorizes child marriage as a form of sexual violence (Article 4 in conjunction with Article 10), allowing for criminal penalties against the perpetrators. However, the TPKS Law does not provide clear criteria for defining child marriage, making its implementation challenging. This research employs a normative method, utilizing a statute approach, conceptual approach, and case approach. In several urban cases, child marriage occurs due to extramarital pregnancies, which are often used as justification by parents to compel their children to marry-despite the child’s unwillingness. The primary reason given is to preserve the family’s honor. Judges typically approve marriage dispensation requests submitted by parents based on the notion of the common good. Such approvals reinforce the assumption that the marriage is consented to by the child, even when the child actually has no other options. In many instances of child marriage, husbands frequently abandon their wives after the marriage ceremony, as their primary motivation for marrying is not to assume responsibility as husbands and fathers. This situation exacerbates the wife’s condition, forcing her to bear the responsibilities of parenthood alone while facing societal stigma. This qualitative prescriptive legal analysis identifies variables that can be used to determine whether a forced marriage can be regarded as sexual violence. These variables also aim to provide certainty in the fair enforcement of the law, particularly for young women, who represent a vulnerable group.